Comparative prospective study of foreign body removal from external auditory canals of cadavers with right angle hook or cyanoacrylate glue. Issue 1 (1st January 2002) - McLaughlin, R; Ullah, R; Heylings, D
Abstract : Objectives: Foreign bodies of the external auditory canal are a relatively common problem in emergency departments. Repeated attempts at removal with standard instrumentation can lead to significant ear injury. Recent case reports of using cyanoacrylate impregnated cotton buds suggest this is less traumatic and well tolerated by patients. No studies on this method have been performed. The objectives of this study were to identify whether there were significant differences in success rate, duration and injury caused by extracting beads from the external auditory canals of adult cadaveric ears using two different methods. This is the first study in a planned series of anatomical and clinical studies relating to foreign body extraction from the external auditory canal. Methods: In this study the success rate, time taken and injury rate were assessed for removal of impacted spherical foreign bodies in the external auditory canals of cadavers using both a blunt right angle hook and cotton buds impregnated with cyanoacrylate glue. This process was performed by a specialist registrar in otolaryngology and repeated by a specialist registrar in emergency medicine. Results: It was shown that both methods had a statistically similar success rate (two tailed binomial test p=0.5) and no injury was identified for either method. In addition the median extraction time for a right angle hook was 6 seconds and 42 seconds for cyanoacrylate. It was also noted that failed extraction was associated with a poor view of the foreign body in the external canal. This was caused by hair, a large tragus or tortuous external canal. Conclusions: The authors feel that cyanoacrylate impregnated cotton buds are as effective at removing impacted foreign bodies as a right angle hook but the process takes longer. It is believed that patients could tolerate this longer time as the cyanoacrylate method is in theory less traumatic.